Memória e etnicidade no Quilombo Ilê Axé Oyá Meguê - Lucia Helena Guerra (Ciências Sociais Unisinos, 2011)
The objective of this article is to analyze the dynamics employed by members of Terreiro Santa Barbara, located in the city of Olinda (PE), to transform the Terreiro of Nation Xambá, considered by many researchers as extinct, as the first Urban Quilombo in Pernambuco and the third one in Brazil. As a starting point based on this reflection I have my Master's thesis in anthropology, this research is based on oral and written sources that indicate that, over the past decades, this religious group has made a great effort to break their historic barriers of isolation and silence. Noting that the leaders of the yard using memory as a collective representation constructed in the present to keep the group coherent and united (Santos, 2003, p. 21) try to show how memories are triggered or oblivious to the needs of the religious group.